Preparing Osteopathic Students for the Single Graduate Medical Education Accreditation System: Evaluating Factors for Match Success in Emergency Medicine - Megan Stobart-Gallagher; Alanna O’Connell (Western Journal of Emergency Medicine, 2018)
Introduction: With the development of and progression toward a single graduate medical education accreditation system combining the current Accreditation Council for Graduate Medical Education (ACGME) and American Osteopathic Association (AOA) residency programs, the total number of students competing for the same postgraduate training spots will continue to rise. Given this increasing competition for emergency medicine (EM) residency positions, understanding factors that contribute to match success is important to ensure a successful match for osteopathic medical students. Methods: Our anonymous survey to evaluate factors that led to a successful match was sent out to residents in current ACGME-, AOA-, and dually-accredited programs via the AOA program director listserv and the Council of Residency Directors (CORD) e-mail listserv in 2017. Results: We had 218 responses. Responses showed that osteopathic graduates had less affiliation with EM residencies, their home institutions provided less information regarding standardized letters of evaluations (SLOE), and that successful osteopathic graduates seemed to learn about them while on EM elective rotations. These students also had less direct EM mentorship and were generally unsatisfied with the level of mentorship available. Osteopathic graduates in current ACGME programs were also more likely to have taken the United States Medical Licensing Examination compared to their AOA resident counterparts. Conclusion: Osteopathic medical schools can improve their graduates’ chances of successfully matching in EM by establishing mentorship programs and educating their students early about SLOEs.